2015
DOI: 10.1007/s11141-015-9586-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined Method for Measuring 3D Wave Spectra. I. Algorithms to Transform the Optical-Brightness Field into the Wave-Height Distribution

Abstract: Although optical tools for measuring the surface-wave characteristics provide the best spatial and temporal resolutions compared with other methods, they face some difficulties while converting the results of indirect measurements into the absolute levels of waves. In this paper, we propose a combined optical method for measuring the 3D spectral density of the heights and the time realizations of the surface-wave profiles. The method involves, first, synchronous recording of the optical-brightness field on a r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several laboratory and open sea studies have shown the effectiveness of the polarimetric approach [8,[10][11][12]. However, the physical models have been shown to be of low accuracy and their use in various open sea and lighting conditions has been shown to be limited.…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory and open sea studies have shown the effectiveness of the polarimetric approach [8,[10][11][12]. However, the physical models have been shown to be of low accuracy and their use in various open sea and lighting conditions has been shown to be limited.…”
Section: Introductionmentioning
confidence: 99%
“…The wave detection parameters include the height, direction and waveform. Based on differences among the measurement methods, wave detection techniques can be classified into various types, such as aerometry, photogrammetric techniques [4], radar measurements [5], electronic measurements [6], optical measurements [7], and acoustic measurements [8]. The photogrammetric method is a non-contact measurement technique; this means that no sensors are launched onto the water surface, and the propagation of waves is not impacted.…”
Section: Introductionmentioning
confidence: 99%